Actinobacillus pleuropneumoniae, surface proteins and virulence: a review - Soto Perezchica, María M.; Guerrero Barrera, Alma L.; Avelar Gonzalez, Francisco J.; Quezada Tristan, Teodulo; Macias Marin, Osvaldo (Frontiers in Veterinary Science, 2023)
Actinobacillus pleuropneumoniae (App) is a globally distributed Gram-negative bacterium that produces porcine pleuropneumonia. This highly contagious disease produces high morbidity and mortality in the swine industry. However, no effective vaccine exists to prevent it. The infection caused by App provokes characteristic lesions, such as edema, inflammation, hemorrhage, and necrosis, that involve different virulence factors. The colonization and invasion of host surfaces involved structures and proteins such as outer membrane vesicles (OMVs), pili, flagella, adhesins, outer membrane proteins (OMPs), also participates proteases, autotransporters, and lipoproteins. The recent findings on surface structures and proteins described in this review highlight them as potential immunogens for vaccine development.